The transformative role of artificial intelligence in modern agriculture - Patel, Hina M. (Review of Artificial Intelligence in Education, 2023)
Objective: To examine the impact and potential of Artificial Intelligence (AI) in revolutionizing traditional agricultural practices to meet the increasing global food demand. Method: A comprehensive review of the integration of AI technologies in agriculture, focusing on advancements in crop cultivation, real-time monitoring, harvesting, processing, and marketing. Results: AI has emerged as a pivotal technology in the agricultural sector, addressing challenges such as climate change, population growth, employment concerns, and food safety. Advanced AI-driven systems have been developed to identify crucial factors, including weed detection, yield estimation, crop quality assessment, and other parameters. These innovations have elevated modern agricultural practices, ensuring enhanced productivity and efficiency. Conclusions: AI holds significant promise in reshaping the future of agriculture. Its potential, combined with machine learning capabilities, presents vast opportunities for the sector's growth. However, the full adoption and integration of AI solutions in agriculture remain a challenge, with the sector still being relatively underserved in terms of AI-driven solutions. Implications: The strategic implementation of AI in agriculture is paramount for the sector's future sustainability. While some advancements are evident, there is a pressing need for more predictive solutions tailored to real-world challenges faced by farmers. Embracing AI will not only ensure increased productivity but also the long-term viability of the agricultural sector.